2009
DOI: 10.1158/0008-5472.can-08-3792
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Epithelial Insulin-like Growth Factor Expression Is a Risk Factor for Lung Cancer Development

Abstract: Insulin-like growth factor (IGF)-I receptor (IGF-IR) signaling has been implicated in several human neoplasms. However, the role of serum levels of IGFs in lung cancer risk is controversial. We assessed the role of tissue-derived IGFs in lung carcinogenesis. We found that IGF-I and IGF-II levels in bronchial tissue specimens containing high-grade dysplasia were significantly higher than in those containing normal epithelium, hyperplasia, and squamous metaplasia. Derivatives of human bronchial epithelial cell l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 44 publications
(46 reference statements)
2
71
0
3
Order By: Relevance
“…Here, we showed that the cell growth-inhibitory activity of BIIB4 and BIIB5 was also more severely compromised at elevated ligand concentrations than that of the BIIB4 and BIIB5 combination. High serum and tumor tissue IGF-I and IGF-II levels have often been observed in cancer patients, and have been associated with disease progression or prognosis (10)(11)(12)(13). Additionally, serum IGF-I levels in cancer patients were reported to increase by severalfold, in some cases exceeding 1,000 ng/mL, after treatment with IGF-IR antibodies (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we showed that the cell growth-inhibitory activity of BIIB4 and BIIB5 was also more severely compromised at elevated ligand concentrations than that of the BIIB4 and BIIB5 combination. High serum and tumor tissue IGF-I and IGF-II levels have often been observed in cancer patients, and have been associated with disease progression or prognosis (10)(11)(12)(13). Additionally, serum IGF-I levels in cancer patients were reported to increase by severalfold, in some cases exceeding 1,000 ng/mL, after treatment with IGF-IR antibodies (47).…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies, such as using a monoclonal antibody (mAb), a dominant-negative mutant, or antisense oligonucleotides, all originally showed that interference of IGF-IR signaling can inhibit tumor growth in animal models (6)(7)(8). In humans, altered expression of IGF-IR, its ligands, and/or IGFBPs is frequently found in a variety of cancers (9)(10)(11)(12)(13), and elevated circulating levels of serum IGF-I are linked with increased risk of developing many cancers (14)(15)(16). In particular, IGF-II upregulation with loss of imprinting is a common event observed in several cancer types (17).…”
Section: Introductionmentioning
confidence: 99%
“…IHC staining procedures were performed as described previously (10). Cytoplasmic expression was blindly analyzed and quantified by two independent pathologists (P.Y.…”
Section: Ihc Staining and Evaluation Of Tmamentioning
confidence: 99%
“…Every 20th 5-m section of the paraffin blocks (20 sections total per mouse) was evaluated after hematoxylin and eosin staining by two pathologists including one animal pathologist. Adenoma and adenocarcinoma were diagnosed according to histological criteria described previously (10).…”
Section: Histology and Ihc Of Mouse Lung Tissuesmentioning
confidence: 99%
See 1 more Smart Citation